Graphene oxide-assisted Co-sintering synthesis of carbon nanotubes with enhanced electromagnetic wave absorption performance. (15th November 2021) - Meng, Rui; Zhang, Tieliang; Liu, Xue; Jiao, Pengzheng; Li, Jianjun; Liu, Liyang; Yuan, Ye; Peng, Qingyu; He, Xiaodong
Abstract: Based on thermal reaction of small organic precursors and solid phase sintering process, 0D CoFe nanoparticle@1D carbon nanotube@2D rGO (reduced graphene oxide) sheet (CoFe-CNT-rGO) electromagnetic wave absorbing composite materials with hierarchical structure are prepared. In the reaction system, citric acid and urea are used as precursors to be adsorbed on the surface of the active alloy particles and gradually form carbon nanotubes. Introduction of graphene oxide (GO) provides "flexible substrate" with oxygen containing groups, which can generate conjugation between iron(III)/cobalt(II) complexes and graphene oxide. Thus, the adjacent molecules can orientate to promote the carbon nanotube growth. In situ template-free process in this research gives an effective and low-cost method for large scale preparation of carbon nanotubes. The prepared CoFe-CNT-rGO hierarchical composite exhibits outstanding electromagnetic wave absorbing ability with the lowest reflection loss reaching −56 dB. Synergistic effect of 2D dielectric carbon sheet, 1D carbon nanotube, 0D CoFe nanoparticles and their corresponding hierarchical structures are responsible for the enhanced electromagnetic wave absorption performance. Graphical abstract: Image 1